Spectral Lines Metcalfe's Law Right? Wrong?. (IEEE spectrum)
This paper discusses the controversy surrounding the soundness of Metcalfe's law. The paper presents an alternate version based on theoretical as well as empirical evidence obtained from a number of tests. Having more than a mathematical significance, the difference of opinion about Metcalfe's law has a direct bearing on the value of dot-com businesses that exploit expanding social networks